IMPACT OF BURNS AND EYE INJURIES ON PATIENTS' QUALITY OF LIFE (REVIEW ARTICLE) - Bilalov E.N.; Нарзикулова К.И.; Mirrakhimova S.Sh.; Oralov B.A.; Sobirova R.U (Western European Studies, 2024)
Burns and injuries to the eye are one of the most serious medical and social problems affecting patients' quality of life. Modern research shows that the consequences of such injuries can range from mild temporary visual impairment to severe ones, leading to permanent vision loss and a significant reduction in quality of life. The question of the impact of burns and eye injuries on various aspects of human life, including physical condition, psycho-emotional wellbeing and social adaptation, is becoming especially relevant
Keywords: adaptation; including; condition; emotional